2001
DOI: 10.1046/j.1439-0523.2001.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of chlorophyll fluorescence to evaluate the cold acclimation and freezing tolerance of winter and spring oats

Abstract: The efficiency of the excitation capture by open Photosystem II (PSII) reaction centres was measured by the Fv/Fm ratios in a collection of winter and spring oats in order to assess the effects of hardening and freezing on the functionality of PSII and also the suitability of a chlorophyll fluorescence‐based method to screen oat cultivars for frost tolerance. A significant reversible decrease in Fv/Fm was found in all genotypes during acclimation to low, non‐freezing temperatures. Fv/Fm analysis appears to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 29 publications
10
109
0
3
Order By: Relevance
“…It is well known that the chlorophyll fluorescence parameter is used to detect and quantify chilling stress by means of changes induced in PSII. F v /F m , as a kind of chlorophyll fluorescence parameter, can be used as an important indicator of injury to PSII (Rizza et al, 2001;Lu et al, 2003;Tambussi et al, 2004;Baker, 2008;Liu et al, 2013;Zhou et al, 2015). Additionally, the present study showed that the application of Spd and SNP significantly decreased chilling-induced electrolyte leakage, compared to the chilling treatment alone.…”
Section: No Involved In Spd-induced Chilling Tolerance In Tomatosupporting
confidence: 62%
“…It is well known that the chlorophyll fluorescence parameter is used to detect and quantify chilling stress by means of changes induced in PSII. F v /F m , as a kind of chlorophyll fluorescence parameter, can be used as an important indicator of injury to PSII (Rizza et al, 2001;Lu et al, 2003;Tambussi et al, 2004;Baker, 2008;Liu et al, 2013;Zhou et al, 2015). Additionally, the present study showed that the application of Spd and SNP significantly decreased chilling-induced electrolyte leakage, compared to the chilling treatment alone.…”
Section: No Involved In Spd-induced Chilling Tolerance In Tomatosupporting
confidence: 62%
“…12 For Arabidopsis thaliana as well as in many other plant species, the chlorophyll fluorescence parameter F v /F m that is widely used as a proxy of the maximum quantum efficiency of PS II photochemistry was found to be highly correlated with low temperature tolerance. [21][22][23][24][25] However, F v /F m measurements overestimates the cold tolerance in Rhododendron ferrugineum L. by 5 °C. 26 Low temperature tolerance of various wheat cultivars was tested using non-imaging fast chlorophyll fluorescence induction kinetics, often called JIP tests.…”
Section: -19mentioning
confidence: 95%
“…Variable fluorescence (Fv) was calculated by subtracting F 0 from Fm. The Fv/Fm ratio measures the efficiency of excitation energy capture by open PSII reaction centers, representing the maximum capacity of light-dependent charge separation in PSII (Rizza et al, 2001).…”
Section: Methodsmentioning
confidence: 99%